Pengaruh Kualitas Produk dan Promosi Penjualan terhadap Keputusan Pembelian di Starbucks Kuta Bali - Veren; Ida Ayu Kalpikawati (JURNAL GASTRONOMI INDONESIA, 2020)
This research aims to investigate (1) the influence of product quality to the purchase decision, the influence of sales promotion to the purchase and the influence of product quality and sales promotion to the purchase decision at Starbucks Kuta, Bali. The sampling technique used in this research is purposive sampling with the total samples of 86 respondents. Data were collected using questionnaire and documentations and was tested their validity and reliability. The data analysis techniques consist of classic assumption test (normality test, multicollinearity test and heteroscedasticity test), multiple linier regression analysis, t test, F test, determination coefficient test and effective contribution by using SPSS for Mac version 23.0 program. The research results showed that product quality and sales promotion simultaneously had positive and significant influence to the purchase decision. Both variables had an influence of 56,6% on purchase decision at Starbucks Kuta Bali.